'Every time I dress myself, it go motherfuckin' viral': Post-verbal flows and memetic hype in Young Thug's mumble rap. Issue 2 (May 2020) - Waugh, Michael
Abstract: Hip-hop studies have historically centred on issues of the 'street' or virtuosic lyricism and flow, foregrounded as evidence of the 'seriousness' of the genre. While these have undoubtedly been valuable theoretical approaches, the prominence of social networking in the 2010s (with its vast implications for communication and identity politics) has sculpted a generation of rappers whose vocal style and self-representation disintegrate prior assumptions about hip-hop identity. These artists, who have flourished in tandem with the rise of streaming services, have been disparagingly dubbed 'mumble rap' by traditionalists owing to the apparent indecipherability of their vocals and a lack of emphasis on observational or poetic lyricism. In this article I argue that this myopic label undervalues the groundbreakingly post-verbal nature of the music being created by these rappers, and highlights the innovations of mumble rap, exploring the centrality of social media, memes and streaming to its existence while critically examining its protagonists' unconventionally stylised vocals. After analysing the impact of streaming, information overload and audience participation (through social media hype and memes) on contemporary hip-hop, I survey the growth of melodic Auto-Tuned vocals and repetitive lyricism in the work of pioneering mumble rappers such as Future, before turning to an extended examination of Atlanta's Young Thug, whose controversially malleable vocal style, which prioritises experimentation with vocal textures while confounding the rules of hip-hop flow, is mirrored by his impulsive exploitation of social media and androgynous fashion sense, establishing him as the most revolutionary archetype of so-called mumble rap.